Alterations of gut microbiota composition in neonates conceived by assisted reproductive technology and its relation to infant growth. Issue 1 (9th November 2020) - Lu, Qun; Lin, Yuan; Chen, Ting; Lv, Hong; Diao, Feiyang; Liu, Cong; Peng, Meijuan; Ling, Xiufeng; Li, Hong; Wang, Yun; Wei, Yongyue; Du, Jiangbo; et al.
ABSTRACT: The gut microbiome in newborns may be strongly influenced by their intrinsic host microenvironmental factors (e.g., the gestational age) and has been linked to their short-term growth and potentially future health. It is yet unclear whether early microbiota composition is significantly different in newborns conceived by assisted reproductive technology (ART) when compared with those who were conceived spontaneously. Additionally, little is known about the effect of gut microbiota composition on weight gain in early infancy. We aimed to characterize the features and the determinants of the gut microbiome in ART newborns and to assess the impact of early microbiota composition on their weight gain in early infancy in mother-infant dyads enrolled in the China National Birth Cohort (CNBC). Among 118 neonates born by ART and 91 neonates born following spontaneous conception, we observed significantly reduced gut microbiota α-diversity and declined Bacteroidetes relative abundance in ART neonates. The microbiota composition of ART neonates was largely driven by specific ART treatments, hinting the importance of fetus intrinsic host microenvironment on the early microbial colonization. Following up these neonates for six months after their births, we observed the effects of gut microbiome composition on infant rapid weight gaining. Collectively, we identified features and determinants of the gut microbiota composition in ART neonates, and provided evidence for the importance of microbiota composition in neonatal growth.